2021
DOI: 10.1097/nne.0000000000001089
|View full text |Cite
|
Sign up to set email alerts
|

Mentoring and Support for Underrepresented Nursing Faculty

Abstract: Background: Nursing faculty members may need several mentors to succeed in scholarly productivity, career development, work-life balance, and socialization in the academy. Underrepresented (UR) faculty report additional challenges to success. Purpose: The aim of this study was to search the literature for best practices in mentoring UR faculty. Methods: An integrative review was conducted to identify best and evidence-based practices for mentoring UR faculty, including gender, sexual minority, race, ethnicity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…The novice nurse educator needs a structured plan and mentoring to develop the competency to teach effectively and remain in academia 30. Benefits of being mentored include increased self-confidence, happiness, and workplace networking with more experienced faculty 31. Moreover, building a mentoring relationship between the new faculty member (mentee) and an experienced educator (mentor) is an ongoing process lasting well beyond the initial orientation phase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The novice nurse educator needs a structured plan and mentoring to develop the competency to teach effectively and remain in academia 30. Benefits of being mentored include increased self-confidence, happiness, and workplace networking with more experienced faculty 31. Moreover, building a mentoring relationship between the new faculty member (mentee) and an experienced educator (mentor) is an ongoing process lasting well beyond the initial orientation phase.…”
Section: Discussionmentioning
confidence: 99%
“…30 Benefits of being mentored include increased self-confidence, happiness, and workplace networking with more experienced faculty. 31 Moreover, building a mentoring relationship between the new faculty member (mentee) and an experienced educator (mentor) is an ongoing process lasting well beyond the initial orientation phase. However, structured mentoring of new faculty was not found to be an integral part of orientation for most respondents in this study.…”
Section: Mentorshipmentioning
confidence: 99%
“…Further, the positive benefits of mentoring programs are seen across undergraduate (Evans et al, 2020 ), graduate (Gitlin & Lypson, 2017 ; Wettemann, 2021 ), medical students (Altonji et al, 2019 ), nursing school (Clement & Welch, 2021 ), advanced training such as residents and fellows (Dawkins & Grier, 2021 ), and faculty (Cranmer et al, 2018 ; Ortiz, 2021 ). The benefits of a mentoring relationship may be particularly helpful for those in underrepresented groups in academic health centers such as male nurses (Ortiz, 2021 ), female pharmacists (Biehle et al, 2021 ), female physicians (Marshall et al, 2020 ), racial minority groups (Dawkins & Grier, 2021 ; Mokel et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…13 Underrepresented minority faculty report the additional stress of often being the only representative for their minority group. 13,14 In previous studies, Black nursing faculty have indicated that they are often burdened and made to feel like the token Black person, without recognition that one person does not represent the entire Black population. 15 Underrepresented minority faculty are often designated as diversity experts.…”
mentioning
confidence: 99%